PETA PERSEBARAN RANDAI DI KABUPATEN KUANTANSINGINGI, PROVINSI RIAU - Fitriana, Yulita; Arpina, Arpina; Irwanto, Irwanto (Universitas Lancang Kuning, 2021)
This study aims to describe the history and distribution of Randai, as well as making Randai’s distribution maps in Kuantansingi Regency, Riau Province. This research is qualitative-descriptive. The data are obtained through field data and library data. Through this research, it is known that the Randai of Kuantansingingi originally comes from Minangkabau and has undergone changes. The acculturation of Minangkabau culture with Malay and change of times has led to changes in stories, language, costumes, dances (joget), musical instruments, and when it is performed, even the view of people on Randai. In the process of making the Randai of Kuantansingingi’s Map in Riau Province, 49 Randai groups were inventoried in various sub-districts in Kuantansingingi Regency. All these Randai groups have been mapped onto the Map of Kuantansingingi’s Randai.